Smarter through Social Protection? Evaluating the Impact of Ethiopia's Safety-Net on Child Cognitive Abilities - Marta Favara; Catherine Porter; Tassew Woldehanna (Institute of Labor Economics (IZA), 2017)
We provide new estimates of the impact of Ethiopia's Productive Safety Net Programme (PSNP) in Ethiopia on child cognitive achievement in the medium term. The programme is the second largest in Africa, and has been rolled out to almost 10 million beneficiaries since 2005. We exploit four rounds of the Young Lives panel data spanning 2002-2013. We find a small but significant effect of the programme on cognitive achievement as measured by numeracy skills. We examine heterogeneity of impacts via "graduation" from the scheme, and find a positive effect on children in households that graduated just before 2013, but none for children in households that remain in the programme.
Keywords: I38; O22; 330; Ethiopia; social protection; children; cognitive development